An analysis of out-of-pocket costs associated with hospitalised injuries in Vietnam. (27th April 2015) - Nguyen, Ha; Ivers, Rebecca; Jan, Stephen; Pham, Cuong
Abstract: Background: Injuries create major financial burden for families. In this study, we estimated the distribution of out-of-pocket payment for medical care of injuries and the role of health insurance in containing such costs. Methods: A prospective cohort study of 892 injured patients admitted to a provincial general hospital between Jan 1, 2010, and Aug 31, 2010, in Vietnam was done. Data for demographic, injury characteristics, and costs by specific categories paid out-of-pocket by patients were included in the analyses. Generalised linear models with log link and gamma distribution were used to examine the associations between insurance status and total medical care costs and specific cost component. Findings: The average total medical care costs paid out-of-pocket by patients during hospital stays were greater than US270 (SD 193). Major drivers of total medical care costs related to surgery (nearly 25%), diagnostic tests or examinations (24%), and drugs (23%). Burn injuries incurred the highest medical care costs during hospital stays (mean US321 [SD 179]) and assault incurred the lowest costs (mean US167 [SD 165]). Total costs were higher for more severe injuries and those that required a higher level of surgery (from US122 for maximum abbreviated injury score [MAIS] of 1 to US485 to MAIS of 5; and US194 for non-surgery, US202 for minor surgery, and US428 for major surgery). Patients using health insurance had lower total costs than those who did not (US245 vs US279). However, no significant associations were noted between health insurance and total costs (p=0·142), costs for surgery (p=0·154), diagnostic tests or examinations (p=0·689), or drugs (p=0·341). Interpretation: This study provides estimates and distribution of costs of medical care for injuries in hospital. Patients and their families seemed to bear all or most of these costs. Although the study highlights the need for ongoing efforts in injury prevention, it also provides further evidence on the few benefits of health insurance in protecting patients and their families from the high costs of hospital stays in Vietnam. Funding: Atlantic Philanthropies.